Reflections on Article 30 of the Trips agreement and lessons from WTO dispute settlement body practice - Hamid Azizi Morad Pour (Faṣlnāmah-i Pizhūhish-i Huqūq-i Khuṣūṣī, 2012)
Article 30of the Trips agreement is relating to the exceptions andlimitation of patent holders. Protection of the holders is thepredominant approach in the Trips agreement meanwhile the maingoal of the Intellectual property rights is to balance the private right ofholders and the interest of societies .one of the main mechanism thatprovided in the Trips to achieve the mentioned goal is use theexceptions which provided in the Article 30but the ambiguous in thisArticle cause the different interpretation between Developed anddeveloping countries. The jurisprudence of dispute settlement body ofthe WTO could not to remove the said ambiguous regarding thedelimitation of private and public interest in the patent system anddespite the dispute settlement body decision regarding the exceptionof the IP holder the contracting state of Trips have differentinterpretation